Women And Physical Violence in The Household During The Covid-19 Pandemic - Margie Gladies Sopacua (JURNAL BELO, 2022)
On April 13, 2020 it was declared a "national disaster" through Presidential Decree No. 12 of 2020 concerning the Determination of Non-Natural Disasters Spreading Corona Virus Disease 2019 (Covid19) as a National Disaster. During the Covid-19 Pandemic, data collected from service institutions or data collection forms for the Women's National Commission (Komnas) were 8,234 cases, the most prominent types of violence against women were in the personal or private sphere, namely domestic violence and personal relations, namely: as much as 79% (6,480 cases). Among them there is violence against wives (KTI) which ranks first 3,221 cases (49%). The government in overcoming criminal acts of violence that occur in the household, especially for women as wives, is one of them by making policies through the promulgation of the PKDRT Law. However, domestic violence cannot be overcome only by the formation of the law. Physical violence is violence in the form of an action which in this case will have an impact on pain by slapping, hitting, kicking and so on which causes minor or serious injury to someone. To overcome the problem of domestic violence against women as wives, it can be seen that the Criminal Law Policy Against Physical Violence for Women in the Household can be carried out through three (3) stages, namely; Pre-emptive efforts are efforts made by the police to prevent the occurrence of criminal acts.